2003
DOI: 10.1111/j.1651-2227.2003.tb00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of respiratory distress syndrome by the microbubble stability test on gastric aspirates in newborns of less than 32 weeks’gestation

Abstract: Aim: There is a need for a rapid method to identify infants who will develop respiratory distress syndrome (RDS) soon after birth, to allow early treatment of affected infants with surfactant. The microbubble stability test (MST) may be one such method, but clinical experience is sparse. Methods: The MST was performed on gastric aspirates from 188 infants with a mean gestational age of 29 (range 23–31) wk. Results: 87 infants developed moderate to severe RDS, corresponding to a prevalence of 46%. The sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…A rapid test of lung maturity that accurately predicts the risk of developing clinically significant RDS would, in the future, allow for early or prophylactic surfactant treatment of infants at risk. 22 As a mode of surfactant administration, the INSURE approach would then provide a means to avoid potentially harmful MV and possibly reduce the need for transfers of moderately preterm infants to an intensive care facility.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid test of lung maturity that accurately predicts the risk of developing clinically significant RDS would, in the future, allow for early or prophylactic surfactant treatment of infants at risk. 22 As a mode of surfactant administration, the INSURE approach would then provide a means to avoid potentially harmful MV and possibly reduce the need for transfers of moderately preterm infants to an intensive care facility.…”
Section: Discussionmentioning
confidence: 99%
“…The SMT is a diagnostic test for RDS that has high sensitivity and specificity . The test is based on the fact that surfactant stabilizes microbubbles <15 μm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…Verder et al [17] used computerized image analyses of the average diameter of microbubbles generated in gastric aspirates to predict RDS in newborns <32 weeks' gestation supported by CPAP soon after birth and found that microbubbles <20 or 25 µm were most predictive of RDS. Fiori et al [15] found the best microbubble count for the diagnosis of RDS was <15/mm 2 .…”
Section: Discussionmentioning
confidence: 99%